2021
DOI: 10.1007/s10995-021-03157-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Abortion Underreporting on Pregnancy Data and Related Research

Abstract: Introduction The impact on research findings that use pregnancy data from surveys with underreported abortions is not well-established. We estimate the percent of all pregnancies missing from women’s self-reported pregnancy histories because of abortion underreporting. Methods We obtained abortion and fetal loss data from the 2006–2015 National Survey of Family Growth (NSFG), annual counts of births from US vital statistics, and external abortion counts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…About 7 percent of the women are assigned to the latent class of women who had had an abortion in the last five years and, among them, about 40 percent did not report having had an abortion in at least one mode. This level of underreporting is consistent with other research, though lower than the rates of underreporting found in comparisons to the Guttmacher Institute abortion providers census [ 4 , 5 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…About 7 percent of the women are assigned to the latent class of women who had had an abortion in the last five years and, among them, about 40 percent did not report having had an abortion in at least one mode. This level of underreporting is consistent with other research, though lower than the rates of underreporting found in comparisons to the Guttmacher Institute abortion providers census [ 4 , 5 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Tourangeau and his colleagues used a sample that included women who were known to have had abortions and found that fewer than 75 percent of them reported ever having had an abortion and only about half reported an abortion during the period in which they were known to have had one [ 7 ]. The problem of underreporting of abortions is not limited to the NSFG; abortions are also underreported in other national surveys in the U.S., including the 1997 National Longitudinal Survey of Youth and the Add Health Study, and in other countries [ 5 , 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study limitations include a nonrepresentative sampling strategy, self-reported data, and social desirability bias common in abortion research. 5 Even so, it is striking that almost one in six medical students reported that either they or their partner had an abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Our study limitations include a nonrepresentative sampling strategy, self-reported data, and social desirability bias common in abortion research. 5 Even so, it is striking that almost one in six medical students reported that either they or their partner had an abortion. Underscoring stressors of medical training, one physician whose partner had an abortion reflected that she, "had 2 abortions (while we were in training).…”
Section: Discussionmentioning
confidence: 99%